Effects of systemic glucocorticosteroids on peripheral neutrophil functions in asthmatic subjects: an ex vivo study - P. L. Paggiaro; L. Bancalari; D. Giannessi; W. Bernini; G. Lazzerini; R. Sicari; E. Bacci; F. L. Dente; B. Vagaggini; R. De Caterina (Mediators of Inflammation)
In 21 asthmatic subjects, several functions of isolated peripheral neutrophils (chemokinesis and chemotaxis toward 10% E. coli; superoxide anion generation after PMA; leukotriene B4 (LTB4) release from whole blood and isolated neutrophtls, before and after different stimuli) were evaluated during an acute exacerbation of asthma, and after 14 – 54 days of treatment with systemic glucocorticosteroids (GCS). During acute exacerbation, superoxide anion generation was higher in asthmatics than in eleven normal subjects (39.2 ± 14.1 vs. 25.2 ± 7.3 nmol, p < 0.05); there was a significant correlation between FEV1 (% of predicted) and neutrophil chemotaxis (r = −0.52, p = 0.04). After treatment, there was no significant change in all neutrophil functions, except for a decrease in neutrophil chemotaxis in subjects who showed an FEV1 increase > 20% after GCS treatment (from 131 ± 18 to 117 ± 21 μm, p = 0.005). Chemokinesis sicantly decreased in all subjects, and the changes significantly correlated with an arbitrary score of the total administered dose of GCS (r = 0.57, p < 0.05). These data suggest that neutrophil activation plays a minor role in asthma, and that treatment with GCS is not able to modify most functions of peripheral neutrophils in asthmatic subjects; chemotaxis seems to be related only to the severity of the asthma and it could reflect the improvement of the disease.